EDUKASI KEBERLANJUTAN STUDI GUNA KETUNTASAN PENDIDIKAN TINGGI BAGI SISWA SEKOLAH MENENGAH ATAS DI PAPUA BARAT: Tinjauan Pendidikan, Karir dan Ekonomi - Rabiudin Rabiudin; Sumarsi Sumarsi; Ekarina Katmas; Karfin Karfin; Almuhaimin Sarnav Ituga (Indonesian Collaboration Journal of Community Services, 2022)
The purpose of this service activity is to provide motivational reinforcement, dissemination of information, and efforts to build awareness of high school students (SMA) equivalent to the urgency of continuing study to university which has implications for education, career, and family economic income. The method of service implementation is carried out in the form of socialization and motivational training in each selected sample school. There are five sample schools with a total target of 12th-grade high school students. The description of this activity is reviewed from the stages of activity planning, implementation, and evaluation of activities. Data collection techniques in evaluating this activity use pre-test and post-test in the form of direct questions about students' interest in continuing their studies in college. The technique of analyzing the results of the evaluation uses a comparison of the number of students who are interested in further studies during pre-training and post-training. The results of this service activity showed that educational activities for the continuation of studies up to university were quite effective. This is evidenced by the increase in the number of students who are interested in further studies after the education or socialization process is carried out. With these results, it is hoped that similar activities will be held in the coming year for different students so that the continuity of study is evenly distributed among all high schools